2022
DOI: 10.3389/fimmu.2022.846155
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Inflammation in Malnutrition Is Driven by Proinflammatory Intestinal Microbiota, Large Intestine Barrier Dysfunction, and Translocation of Bacterial Lipopolysaccharide

Abstract: Acute malnutrition, or wasting, is implicated in over half of all deaths in children under five and increases risk of infectious disease. Studies in humans and preclinical models have demonstrated that malnutrition is linked to an immature intestinal microbiota characterized by increased prevalence of Enterobacteriaceae. Observational studies in children with moderate acute malnutrition (MAM) have also observed heightened systemic inflammation and increased circulating bacterial lipopolysaccharides (LPS; endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Recently, we demonstrated an increase in basal inflammatory cytokines, impaired intestinal barrier function, circulating endotoxin, and an exaggerated response to inflammatory stimuli in children with MAM ( 10 ). Similar features are reported in our studies in a mouse model that mimics the features of MAM ( 11 ). These features were associated with the development of a proinflammatory intestinal microbiota.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Recently, we demonstrated an increase in basal inflammatory cytokines, impaired intestinal barrier function, circulating endotoxin, and an exaggerated response to inflammatory stimuli in children with MAM ( 10 ). Similar features are reported in our studies in a mouse model that mimics the features of MAM ( 11 ). These features were associated with the development of a proinflammatory intestinal microbiota.…”
Section: Introductionsupporting
confidence: 90%
“…Therefore, we used an established mouse model of MAM ( 37 41 ) to investigate the impact of an acute infectious or inflammatory challenge on bone marrow and bone health. In this model, malnutrition led to systemic inflammation, impaired intestinal barrier function, circulating endotoxin, and an exaggerated response to inflammatory stimuli that promoted weight loss ( 11 ). Here we show that malnutrition also conditions the bone marrow for an altered response to 2 different inflammatory stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are likely other contributors to parasite dissemination in the malnourished mice since we observed that splenic infection was not completely abrogated when CCR7-deficient monocytes were transferred to the dermal site of infection. Collectively, these data indicate that parasite-induced production of PGE 2 , which is part of an exaggerated inflammatory response in the malnourished host [ 70 , 71 ], amplifies CCR7-dependent trafficking of parasite-bearing inflammatory monocytes to the visceral organs. In contrast, PGE 2 -mediated enhancement of the infection in neutrophils was localized and did not influence L .…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of Firmicutes to Bacteroidota (F/B) is an important indicator to describe the structure of intestinal flora. The high-fat diet promotes the production of LPS and increases the F/B ratio [ 68 , 69 , 70 ]. Clinical studies have shown that the abundance of Bacteroidota in the intestinal bacteria of the elderly is reduced [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%